Evaluating policies and regulations used to control corruption among accounting officers in the public sector of South Africa: a systematic literature review - Vorster, Hester; Nwosu, Lilian (Frontiers in Sociology, 2024)
Corruption, a global phenomenon, affects countries worldwide, transcending geographic and political boundaries, and continues to escalate, partly due to the inefficiency of financial and legal institutions and lack of enforcement. This has significant implications for Africa, hindering democracy, development, and poverty alleviation efforts. Defined as the intentional misuse of official authority for personal benefit, corruption is often fueled by public sector financial managers or accounting officers embezzling funds. The increasing pressure on these officers to justify public fund usage, coupled with expectations for effective service delivery, may contribute to corrupt practices. This article presents a systematic literature review focused on evaluating policies and regulations to control corruption among accounting officers in South Africa’s public sector. The public sector in South Africa has recently seen a rise in corruption cases, with numerous incidents involving corrupt government officers, including accounting officers, gaining media attention. This situation prompted the need for the study, which systematically reviewed existing literature to identify gaps and weaknesses in current policies and regulations. The findings revealed non-compliance with anti- corruption policies and regulations, along with a lack of accountability among accounting officers. Additionally, the study observed that punishment measures for those implicated in misusing public funds are inconsistently implemented, highlighting a significant gap between policy and practice. These findings are critical for government policymakers, as they reveal areas needing improvement in anti-corruption policies and regulations. Issues identified include unqualified officers, poor delegation, embezzlement, and non-compliance. The study recommends that the government consistently apply strict measures against officials guilty of corruption, holding them accountable for their actions. It also advocates for the implementation of effective monitoring and evaluation systems to enforce anti-corruption policies and bridge the policy-practice gap. Emphasizing that good planning is as crucial as the implementation structures themselves, the study suggests that effective functioning requires both elements to work in tandem.